PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI ALAT PERAGA KERTAS LIPAT TENTANG MENGENAL ARTI PECAHAN PADA SISWA KELAS IV SD NEGERI 023 RAMBAH HILIR TAHUN PELAJARAN 2017/2018 - Joko Suprapto (STKIP Rokania Pasir Pangaraian, 2019)
In learning Mathematics About recognizing the meaning of Fractions by using Fold paper props. with folding paper tools obtained student learning outcomes are increasing and meet the minimum completeness criteria that have been determined. The teaching aids used by each teacher are diverse, one of which is teaching aids that are used to add and improve student learning achievement. Classroom Action Research (CAR) is divided into two cycles using the Classroom Action Research (CAR) design which is divided into two cycles. Each cycle consists of 4 (four) stages, namely: (1) Improvement Plan, (2) Implementation of Improvement, (3) Data Collection, (4) Reflection. The study was conducted at SDN 023 Rambah Hilir, Rambah Hilir Subdistrict, Rokan Hulu Regency, with the number of class IV students as many as 20 students consisting of 8 male students and 12 female students. The results of the study before the cycle showed students still did not master the material, especially in determining the meaning of fractions, in the process obtained a completeness value of 40% while in the first cycle the achievement of completeness results was 60%, in the second cycle achieving 95% completeness proved that after using paper folding props active students in teaching and learning activities. From the results of these studies it is clear that by using folding paper props can improve student learning achievement in learning Mathematics Students SD N 023 Rambah Hilir, especially in identifying fractions